Gender, Sainthood, and Everyday Practice in South Asian Shi'ism - Ruffle, Karen G. (Book collections on Project MUSE., 2011)
This study of devotional hagiographical texts and contemporary ritual performances of the Shi'a of Hyderabad, India demonstrates how traditions of sainthood and localised cultural values shape gender roles. The author focuses on the annual mourning assemblies held to commemorate the battlefield wedding of Fatimah Kubra and her warrior-bridegroom Qasem, martyred in battle before their marriage was consummated. She argues that hagiography, an important textual tradition in Islam, plays a dynamic role in constructing the memory, piety, and social sensibilities of a Shi'i community.